2014
DOI: 10.1089/hgtb.2013.176
|View full text |Cite
|
Sign up to set email alerts
|

K137R Mutation on Adeno-Associated Viral Capsids Had Minimal Effect on Enhancing Gene DeliveryIn Vivo

Abstract: The adeno-associated viral (AAV) vector has emerged as an attractive vector for gene therapy applications. Development of AAV vectors with enhanced gene transduction efficiency is important to ease the burden of AAV production and minimize potential immune responses. Rational mutations on AAV capsids have gained attention as a simple method of enhancing AAV transduction efficiency. A single-amino acid mutation, K137R, on AAV1 and AAV8 was recently reported to increase liver transgene expression by 5-10-fold. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…We also concur with Xiao and colleagues 33 and their conclusion that additional variables, such as the sensitivity of the reporter genes, the vector titers, and the vector potency, could also be major factors. These results, nonetheless, underscore the need to exercise caution in relying on, and interpreting data from, experimental rodent models, as well as the need for pursuing additional studies using non-human primate models to delineate the role of each of the critical Y, S, T, and K residues to get at the underlying molecular mechanism of the observed differences in the transduction efficiency of these mutant AAV8 vectors in various tissues in general and hepatocytes in particular.…”
Section: Human Gene Therapy Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…We also concur with Xiao and colleagues 33 and their conclusion that additional variables, such as the sensitivity of the reporter genes, the vector titers, and the vector potency, could also be major factors. These results, nonetheless, underscore the need to exercise caution in relying on, and interpreting data from, experimental rodent models, as well as the need for pursuing additional studies using non-human primate models to delineate the role of each of the critical Y, S, T, and K residues to get at the underlying molecular mechanism of the observed differences in the transduction efficiency of these mutant AAV8 vectors in various tissues in general and hepatocytes in particular.…”
Section: Human Gene Therapy Methodssupporting
confidence: 89%
“…32,33 Whereas Jayandharan and colleagues 32 reported that a single lysine-mutant (K137) of scAAV8-EGFP vector increased the transduction efficiency by 11-fold in hepatocytes in C57BL/6J mice, Xiao and colleagues, 33 using the same K137R-AAV8 mutant vectors expressing either the LacZ or the …”
Section: Human Gene Therapy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study on Y to F mutants of both AAV8 and AAV-DJ also displayed minimal enhancement of gene expression in vivo (to be published). Furthermore, Qiao et al also obtained negative results of K137R on AAV8 [ 34 ], which were reported to enhance gene expression by 5 to 10 fold in liver [ 15 ]. These inconsistent results may be caused by using different reporters contributing to various measurements of transduction efficiency, incorrect vector titers, dilutions, and/or inconsistent vector potency from batch to batch.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, this issue is very significant because the presence of neutralizing antibodies against the AAV serotype limits the potential clinical candidates for the gene therapy [15▪]. Over the past years, significant effort has been put into the development of AAV variants that circumvent the effect of neutralizing antibodies [14,16]. Recently, a chimeric AAV vector developed by capsid reengineering was shown to effectively transduce the heart for the first time in a clinically relevant large animal model [17▪].…”
Section: Adeno-associated Virus For Gene Therapymentioning
confidence: 99%